No evidence for decreased D2/3 receptor availability and frontal hypoperfusion in subjects with compulsive pornography use. (30th May 2021) - Stormezand, Gilles N.; Doorduin, Janine; Chaves, Lumi T.; García, David Vállez; Nienhuis, Fokko J.; Schoevers, Robert A.; Kremer, Berry P.H.; Booij, Jan; Dierckx, Rudi A.J.O.
Highlights: Compulsive use of pornography may lead to problems in several domains. It is currently unknown whether the use of pornography may become addictive. No decrease in D2 receptor availability in subjects with compulsive pornography use. Cerebral blood flow in frontal regions similar to healthy controls. Abstract: Pornographic addiction refers to an addiction model associated with compulsive and repeated use of pornographic material. Whether the use of pornography may indeed become addictive remains a matter of debate. The current study investigated whether compulsive pornography use (CPU) is accompanied by reduced D2/3 receptor availability in the striatum and frontal hypofunctionality. Male subjects between 18 and 50 years of age with and without CPU were recruited using online and newspaper advertisements. Questionnaires were used to the assess the severity of compulsive pornography use (CIUS) and symptoms of depression, impulsivity and sensation seeking. Dopaminergic imaging was performed using [11C]-raclopride PET. Striatal binding potentials (BPND) and regional frontal cerebral influx values (R1) of [11C]-raclopride were calculated. Arterial Spin Labeling (ASL) MRI was performed to assess regional cerebral blood flow. No group differences between striatal BPND's of [11C]-raclopride in subjects with ( n  = 15) and without ( n  = 10) CPU were detected. In CPU subjects, no correlation was found between the CIUS score and striatal BPND's. Cerebral R1 values in frontal brain regions and cerebral blood flow measurements did not differ between groups. The current study fails to provide imaging support for sharing similar neurobiological alterations as previously has been reported in other addictive modalities.